The potential role of the thymus in immunotherapies for acute myeloid leukemia - Hino, Christopher; Xu, Yi; Xiao, Jeffrey; Baylink, David J.; Reeves, Mark E.; Cao, Huynh (Frontiers in Immunology, 2023)
Understanding the factors which shape T-lymphocyte immunity is critical for the development and application of future immunotherapeutic strategies in treating hematological malignancies. The thymus, a specialized central lymphoid organ, plays important roles in generating a diverse T lymphocyte repertoire during the infantile and juvenile stages of humans. However, age-associated thymic involution and diseases or treatment associated injury result in a decline in its continuous role in the maintenance of T cell-mediated anti-tumor/virus immunity. Acute myeloid leukemia (AML) is an aggressive hematologic malignancy that mainly affects older adults, and the disease’s progression is known to consist of an impaired immune surveillance including a reduction in naïve T cell output, a restriction in T cell receptor repertoire, and an increase in frequencies of regulatory T cells. As one of the most successful immunotherapies thus far developed for malignancy, T-cell-based adoptive cell therapies could be essential for the development of a durable effective treatment to eliminate residue leukemic cells (blasts) and prevent AML relapse. Thus, a detailed cellular and molecular landscape of how the adult thymus functions within the context of the AML microenvironment will provide new insights into both the immune-related pathogenesis and the regeneration of a functional immune system against leukemia in AML patients. Herein, we initially review the available evidence supporting the potential correlation between thymic dysfunction and T-lymphocyte impairment with the ontogeny of AML (II-VI). We then discuss how the thymus impacts current and future therapeutic approaches in AML (VII). Finally, we review various strategies to rejuvenate thymic function in adulthood to improve the precision and efficacy of cancer immunotherapy (VIII).